Investigation of Pharmacokinetic Data of Hypericin, Pseudohypericin, Hyperforin and the Flavonoids Quercetin and Isorhamnetin Revealed from Single and Multiple Oral Dose Studies with a Hypericum Extract Containing Tablet in Healthy Male Volunteers - Schulz, Hans-Ulrich; Schürer, Michael; Bässler, Dagmar; Weiser, Dieter (Arzneimittelforschung, 2005)
Hypericins, hyperforin and flavonoids are discussed as the main components contributing to the antidepressant action of St. John’s wort (Hypericum perforatum). Therefore, the objective of the two open phase I clinical trials was to obtain pharmacokinetic data of these constituents from a hypericum extract containing tablet: hypericin, pseudohypericin, hyperforin, the flavonoid aglycone quercetin, and its methylated form isorhamnetin. Each trial included 18 healthy male volunteers who received the test preparation, containing 900 mg dry extract of St John’s wort (STW 3-VI, Laif ® 900), either as a single oral dose or as a multiple once daily dose over a period of 14 days. Concentration/time curves were determined for the five constituents, for 48 h after single dosing and for 24 h on day 14 at the end of 2 weeks of continuous daily dosing. After single dose intake, the key pharmacokinetic parameters were determined as follows: Hypericin: Area under the curve (AUC(0- ∞)) = 78.33 h · ng/ml, maximum plasma concentration (Cmax) = 3.8 ng/ml, time to reach Cmax (tmax) = 7.9 h, and elimination half-life (t1/2) = 18.71 h; pseudohypericin: AUC(0- ∞) = 97.28 h · ng/ml, Cmax = 10.2 ng/ml, tmax = 2.7 h, t1/2 = 17.19 h; hyperforin: AUC(0- ∞) = 1550.4 h · ng/ml, Cmax = 122.0 ng/ml, tmax = 4.5 h, t1/2 = 17.47 h. Quercetin and isorhamnetin showed two peaks of maximum plasma concentration separated by about 3 – 3.5 h. Quercetin: AUC(0- ∞) = 417.38 h · ng/ml, Cmax (1) = 89.5 ng/ml, tmax (1) = 1.0 h, Cmax (2) = 79.1 ng/ml, tmax (2) = 4.4 h, t1/2 = 2.6 h; isorhamnetin: AUC(0- ∞) = 155.72 h · ng/ml, Cmax (1) = 12.5 ng/ml, tmax (1) = 1.4 h, Cmax (2) = 14.6 ng/ml, tmax (2) = 4.5 h, t1/2 = 5.61 h. Under steady state conditions reached during multiple dose administration similar results were obtained. Further pharmacokinetic characteristics calculated from the obtained data were the mean residence time (MRT), the lag-time, the peak-trough fluctuation (PTF), the lowest observed plasma concentration (Cmin), and the average plasma concentration (Cav). The data obtained for the five consitituents generally corresponded well with values previously published. The trial preparation was well tolerated.
Keywords: Antidepressant; Flavonoids; Hyperforin; Hypericin; Hypericum perforatum; Laif® 900; Pseudohypericin; STW 3-VI, pharmacokinetics